Pathways to high-impact journal publication: mastering bibliometric analysis in four steps / Yii Ming Leong and Yeo Jiin Yih - Yii, Ming Leong; Yeo, Jiin Yih (2023)
Bibliometric analysis is a research method that summarises extensive bibliometric data. It enables scholars to identify emerging trends in article and journal performance, collaboration patterns, publication trend analysis, author productivity, citation analysis and predicting emerging trends. Mastering bibliometric analysis involves four key steps. Firstly, identify the topic of interest; secondly, narrow down the scope; thirdly, download the dataset;and finally, conduct the bibliometric analysis and present the results. Bibliometric analysis enables academicians to excel in their Key Performance Indicators (KPIs) by publishing high-impact journals. It also increases their visibility and global recognition as well as creating avenues for securing funding opportunities. Furthermore, bibliometric analysis showcases the novelty of its usefulness in research. First, datasets are readily available and many research analytical tools are openly accessible, making it applicable across a broad spectrum of academic disciplines. Additionally, simplicity in analysis, minimal resource requirements and methodological transparency further enhance its practicality, providing a cost-effective and efficient approach for researchers. In terms of commercialization potential, empowering the application of bibliometric analysis leads to ncome generation avenues. This encompasses organizing paid workshops and training sessions to educate researchers on effective use of bibliometric insights. Additionally, offering paid consultation services aids researchers and institutions in strategically leveraging bibliometric data for planning, while providing paid research evaluation packages supports funding agencies and institutions in assessing research impact.